UTILIZATION OF INTERNET OF THINGS (IoT) FOR ENERGY EFFICIENCY IN SMALL AND MEDIUM RETAIL BUSINESSES - Dison Librado; Dixian Bhikuning; Dara Kusumawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Energy costs and sustainability pressures have encouraged retail businesses to adopt technologies that optimize electricity usage without reducing customer comfort. Internet of Things (IoT) enables real-time monitoring and control of electrical devices through sensors and network connectivity, offering new opportunities for energy management in retail stores. This paper aims to analyze the potential utilization of IoT for energy efficiency in small and medium retail businesses by discussing the conceptual design, implementation scenarios, and indicative benefits. The research employs a qualitative-descriptive approach based on literature review and scenario modeling for typical energy uses in retail, namely lighting, air conditioning, and main electrical equipment. The proposed IoT architecture consists of three layers: device layer (sensors and actuators), network and gateway layer, and application and analytics layer. Implementation scenarios include presence-based lighting control, schedule and temperature-based air conditioning control, and smart load monitoring to detect anomalies. A simple comparative illustration between conventional and IoT-enabled operations indicates that automation and data-driven control can reduce operating hours of selected devices, which translates into potential savings in kWh and electricity costs, while also supporting green business objectives. The findings provide a conceptual and practical reference for retail business owners, SME development programs, and technology providers to design digital green innovation initiatives in the retail sector.